Revolucionarios y bandidos: La trayectoria villista en la Revolución Mexicana - Lopes, Maria Aparecida de S. Abigeos [UNESP] (My University, 2005)
In the last decades of the 19 th century the Mexican society went through a period of political and economical stability, and relative social tranquility. On contrast, during the revolutionary context various armed movements promoted the disruption of this status quo. In this article, by the analysis of several testimonies, I intend to show some aspects regarding criminality and violence phenomena, during the 1910 and 1920 years on the Northern Mexico.
Revolutionaries and bandits: Villist trajectory in the Mexican Revolution
Keywords: Banditry; Criminality; Mexican Revolution